Physicochemical stability of oleogel-in-water emulsions loaded with β-carotene against environmental stresses. (1st February 2022) - Zhang, Ruoning; Cui, Mengnan; Ye, Jingjin; Yuan, Dongdong; Mao, Like
Abstract: Oleogel-in-water emulsions were prepared using monoglyceride (GMS) oleogel as the oil phase and tween-20 (TW) as the emulsifier. The roles of TW content in the emulsions over the change in temperature, ionic strength, pH and against freeze-thawing were evaluated. Particle size of the emulsions decreased with the increase in emulsifier content. With the development of GMS structures in emulsions, both shearing viscosity and storage modulus of the systems were enhanced. Only minor size changes in emulsions with higher TW content were observed after thermal treatment. The increase in ionic strength of emulsions led to increase in droplet size, but the presence of TW inhibited phase separation. All the emulsions were stable by changing pH from 6 to 10. Significant increases in droplet size were observed when the emulsions were subjected to three cycles of freeze-thawing, but only slight oiling off was detected. When β-carotene (3% in the emulsion) was incorporated within oleogel-in-water emulsions, it was better retained in the systems with higher TW content, either subjected to thermal treatment or light exposure. These findings suggested that oleogel-in-water emulsions had good physical stability over changes in pH, ionic strength, and temperature, and were able to protect high loading of lipophilic bioactives. Highlights: Properties of oleogel-in-water emulsions were dominated by GMS and TW. The emulsions had good stability against environmental stresses. TW (>1%) could better protect high loading of β-carotene.